Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. Performance Development of Islamic School’s Principals in Republic of India in the light of educational Competencies Mr. Badruddin Mohammad Saleem, Prof. Abdullah Mohammad Al-Manea 2. The impact of the shortage of educational supervisors in the Jerusalem Education Directorate on the quality of teaching Ms. Dima Yousef Atoun, Dr. Ibrahim Arman 3. The Role of School Principal’s Strategic Vision in Achieving Organizational Excellence: An Analytical Study of Secondary Schools Ms. Sondos Naif Ezzdeen Alulaime 4. Patterns of administrative practices for secondary school principals in the southern governorates of Palestine Dr. Heba Uqelan Abed Al-Aziz Elyan 5. The reality of educational supervision in following up the educational process based on distance education in the city of Jeddah from the supervisors’ point of view Mrs. Amal Ali Mofraq Al-Shehri, Dr. Rabab Al-Harbi 6. Effect of the perspectives of intellectual disabilities teachers towards the absence of job security and its impact in day care centers Mrs. Ebtisam Saeed Al-Sihli, Dr. Walaa Abdullah Khares 7. Parent-child Relationship in the Digital Era Ms. Suzan Muhammad Abu Hilal, Prof. Iyad Saleem El-Halaq